JANUBIY OROLBO‘YI QAZUVCHI ARILARI (SPHECIDAE, CRABRONIDAE) IMAGOLARINING FENOLOGIK XUSUSIYATLARI - Embergenov, M.A.; Medetov, M.J.; Saparov, Q.A.; Saparov, A.D.; Tajibayeva, J.D. (SCIENCE and SOCIETY, 2024)
This article describes 61 species of digger wasps (Sphecidae, Crabronidae), common in the Southern Aral region, and provides information on the phenological aspect of the adults of these species. Digger wasps common in this area are divided into spring, spring-summer, summer and polycyclic species.
Keywords: digger wasp; Sphecidae; Crabronidae; South Aral Region; phenology